Srpenica seismites - indicators of paleoseismicity in the Upper Soča valley, NW Slovenia - Marjanac, Tihomir; Marjanac, Ljerka; Poljak, Marijan; Živčič, Mladen; Bavec, Miloš (Geologija, 2001)
Varve-like lacustrine sediments of Pleistocene to Holocene age were studied in the abandoned clay pit near Srpenica in the Upper Soča valley. Within a sequence of laminated to thin bedded lacustrine deposits, two intervals of soft-sediment deformations were studied and interpreted herein in terms of seismites. The age of deformation is estimated by a radiocarbon date of wood (at the top of the lower deformed layer) at 12790±85 14C years BP, and the genesis is attributed to strong past earthquakes, which is very much in accordance with the present seismicity of the studied area.